2021
DOI: 10.1007/s11661-020-06110-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silicon on Corrosion of Directional Fe-B-Si Alloy in Liquid Zinc

Abstract: The effect of Si on the corrosion of an Fe-B-Si alloy in liquid zinc was investigated. Corrosion tests of Fe-B-Si were conducted in a pure zinc bath (99.99 wt pct Zn). The results indicated that Si in a-Fe phase had a significant effect on the structure and evolution of corrosion interfaces in a directional Fe-B-Si alloy immersed in liquid zinc. Moreover, Si enrichment of the corroded interface induced changes in the mode of element diffusion, thereby affecting the Fe-Zn reaction and the quantity and volume of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Furthermore, the orientation and size of the hard phases in cast irons can strongly determine the mechanical and wear-reisitant properties of the materials, which may depend on the alloying elements and solidification rates to refine the microstructures [ 30 , 31 ]. Liu et al investigated the effect of Si on the corrosion resistance of DS Fe-B alloy in static liquid zinc, and found that Si improves the corrosion resistance to liquid zinc [ 32 ]. Prince Setia et al found that ~4 wt.% Si addition into stainless steel can give rise to phase transformation from a single-phase austennite to duplex microstructure of ferrite and austenite owing to the ferrite stabilizer effect of Si, e.g., the increase in the activity of carbon and solid solution strengthening of the Si addition [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the orientation and size of the hard phases in cast irons can strongly determine the mechanical and wear-reisitant properties of the materials, which may depend on the alloying elements and solidification rates to refine the microstructures [ 30 , 31 ]. Liu et al investigated the effect of Si on the corrosion resistance of DS Fe-B alloy in static liquid zinc, and found that Si improves the corrosion resistance to liquid zinc [ 32 ]. Prince Setia et al found that ~4 wt.% Si addition into stainless steel can give rise to phase transformation from a single-phase austennite to duplex microstructure of ferrite and austenite owing to the ferrite stabilizer effect of Si, e.g., the increase in the activity of carbon and solid solution strengthening of the Si addition [ 27 ].…”
Section: Introductionmentioning
confidence: 99%